A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) from Yunnan, China - Li, Guo-Feng; Zheng, Fa-Ke (Zootaxa, 2011)
The genus Oxyporus Fabricius was established by Fabricius in 1775 with Staphylinus rufus Linné as the type species. Prior to this study, 114 species of the genus were known worldwide in the Palaearctic, Oriental, Nearctic and Neotropical Regions (Herman, 2001). In the subgenus Oxyporus, 37 species were hitherto known to occur in China (Bernhauer, 1933, 1938, 1943; Alekandrov, 1933, 1934; Adachi, 1939; Hayashi, 1975, 1985; Zheng, 1992, 1997, 2010; Li, 1992, 1993; Huang et al., 2005, 2006), with 30 recorded from Mainland China and 7 from Taiwan. However, only 3 species have been reported from Yunnan, China. During this study on the Oxyporus of Yunnan, we found that our specimens represent a new species. Herein, we describe Oxyporus (Oxyporus) puerius sp. nov. and provide color images of the habitus and aedeagus.